'Is this the tallest building in the world?' A posthuman approach to ethical dilemmas in young children's learning projects. Issue 3 (September 2016) - Palmer, Anna
In this article, I explore alternative ways of understanding ethics in preschool. In this, I draw on a posthumanist understanding of ethical concerns as entangled intra-actions of the world, rather than as a human affair. The examined data are part of an ongoing preschool project called 'Children's relations to the city', in which children begin to investigate tall buildings in the immediate vicinity of the preschool and then turn their attention to other larger and more famous buildings in the world, such as Burj Khalifa, the World Trade Centre and Tapei 101. At first, the children seem to be interested in mathematics and science and collaboratively measure and compare the towers shown on pictures. The project then changes gear, and the children ask questions about the living conditions in faraway countries. This transfers the project from the local preschool to a global world in which complex ethical dilemmas emerge. The article discusses the ethics that can emerge when understanding children's play and learning in preschool as always and already ethical and entangled with a more-than-human global world.